Munchausen syndrome by proxy presented as recurrent respiratory arrest and thigh abscess: a case study and overview - Foto-Özdemir, Dilşad; Yalçın, Sıdıka Songül; Zeki, Ayşe; Yurdakök, Kadriye; Özusta, Şeniz; Köse, Aslıhan; Karadağ, Ferda; Yıldız, İrem and Balseven-Odabaşı, Aysun and Kale, Gülsev (The Turkish Journal of Pediatrics, 2013)
While many physicians are familiar with the sexual or physical abuse of children, there is little awareness about Munchausen syndrome by proxy (MSBP). As case reports of MSBP increase, awareness among physicians is thought to increase as well. We thus present herein a 16-month-old girl who admitted to Hacettepe University İhsan Doğramacı Children’s Hospital with the complaint of seizure, recurrent apnea and thigh abscess, who was later diagnosed as MSBP. The case was being followed by the Child Protection Team of the hospital (Haceteppe University Child Protection Unit [HU-CPU]). HU-CPU contributed to the early detection of this case and protected the child from a possible fatal outcome. The mother was confronted for MSBP and refused to take responsibility for her child’s symptoms. As seen in this case, when MSBP is suspected, psychiatric evaluation of the mother, evaluation of the mother-child interaction and collection of a detailed family and social history can have a positive impact on the prognosis in these cases. This case report underlines the importance of multidisciplinary team work to share the responsibility and reduce the burden during the treatment process of these difficult and complicated cases.